Patterns of Cultural Adaptation in Marriage and Funeral Customs between Javanese and Acehnese Ethnic Groups in Sukadamai Village, Aceh Besar - Asmanidar, Asmanidar (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2025)
This study aims to analyze the cultural adaptation patterns of the Javanese community in their interaction with the Acehnese community in Gampong Sukadamai, Lembah Seulawah District, Aceh Besar Regency, particularly within the context of marriage and death rituals. This research employs a qualitative approach using observation, in-depth interviews, and documentation as data collection techniques. The findings reveal that cultural adaptation occurs gradually through social interaction, participation in communal and religious activities, and cooperation in economic practices. In the socio-cultural sphere, harmonious acculturation emerges, evidenced by the integration of Javanese and Acehnese elements in marriage rituals, communal feasts, and death ceremonies. The main challenges in adaptation involve differences in language, customs, and cultural values; however, these are overcome through effective communication, negotiation, and continuous interaction. In conclusion, the adaptation process forms a new multicultural identity that strengthens social cohesion, tolerance, and interethnic cooperation in Gampong Sukadamai